Orthodox Churches and States in Europe: Problems and Perspectives (Stato, Chiese e pluralismo confessionale, 2023)
ABSTRACT: The article offers a careful analysis on the way the end of the USSR and the growth of the Orthodox presence in the European Union have challenged the concept of canonical territory. In the West, this has produced a phenomenon of the territorialization of the exercise of religious freedom. It is examined how the potential access to the EU of Ukraine, Moldova, Albania and Northern Macedonia will influence the relevance of these Churches in the relations that the Union maintains with them in application of art. 17 TFUE. Indeed, this relation is strengthened by the great consistency of the Orthodox diaspora in the West and by the development and growth of Eparchies abroad, created by the respective national Churches. Therefore, it is appropriate to reflect on the need for identifying self-preservation of all religions and in particular of the Orthodox one, in order to guarantee the balance and orderly development of the Union's institutional political system in a relationship compatible with the needs of separation and secularism of the States. Two key factors are the political crisis of the USSR and the granting of autocephaly to the ecclesiastical communities operating in the states which had become sovereign: this has weakened the Moscow Patriarchate and its role in the Orthodox ecumenical system; at the same time, the ecumenical patriarchate, which claims its exclusive right to grant autocephaly, has proceeded to “contractualize” the nature of his primacy through the structure of the Tomas.